Neuropsychological performance profiles in groups with harm avoidance (HA) and novelty seeking (NS) temperament trait clusters : an exploratory study - natalie@7i.co.za (University of Pretoria, 2013)
Mini Dissertation (MA (Clinical Psychology))--University of Pretoria, 2010.